Markovian Decision Processes with Probabilistic Observation of States - Satia, J. K.; Lave, R. E. (Management Science, 1973)
This is a study of finite state discrete time discounted Markovian decision process when the states are probabilistically observed. A model of this process is formulated, and an implicit enumeration algorithm is presented which optimizes the total expected discounted reward given the initial state. Several numerical examples are presented.